ZnO nanorods-PANI heterojunction dielectric, electrochemical properties, and photodegradation study of organic pollutant under solar light. (11th June 2021) - Belabed, C.; Tab, A.; Moulai, F.; Černohorský, O.; Boudiaf, S.; Benrekaa, N.; Grym, J.; Trari, M.
Abstract: In the last years, the development of photocatalysts has gained a growing interest in the photoelectrochemical conversion. Here, we report a hetero-junction organic/inorganic (Polyaniline (PANI)) on n type Silicon substrate prepared by electrophoretic deposition (EPD). ZnO nanorods ( NRs ) are grown by chemical bath deposition (CBD) on seed layer of ZnO prepared by dip coating onto the PANI layer. The relief and morphological properties are investigated by both atomic force microscope (AFM) and scanning electron microscopy (SEM). The forbidden bands ( E g ) of 1.12 and 3.26 eV are obtained for PANI and ZnO NRS respectively. The optical and dielectric constants are determined by the diffuse reflectance where the extinction coefficient ( k ), the refractive index ( n ), optical conductivity, dissipation factor and relaxation time are extracted. The semi conductivity is highlighted by the capacitance measurement; a flat band potential (Efb  = 0.541 V) for ZnO NRs -PANI is deduced from the Mott-Schottky plot. The contributions of the bulk and grain boundaries of the electrode are evidenced from the electrochemical impedance spectroscopy (EIS). The as-fabricated samples show improved photoactivity compared to PANI and ZnO NRs . Indeed, the hetero-junction exhibits a high stability and recyclability for the photodegradation of Orange II (OII) after six cycling runs. The current research offers a new understanding of designing a high performance of the photocatalyst under solar light based on PANI for the wastewater treatment. Highlights: The work deals with the photodegradation on ZnO NRs -PANI under solar light of Orange II, a hazardous dye for the first time. The solar photocatalysis over the hybrid-system exhibits an increased performance in the Orange II. A first order kinetic was found with a half photocatalytic-life 46.8 min. The deactivation of the catalyst remained neglected after the sixth cycle and the initial photoactivity was fully restored.